Decision-Making for Tourism Destinations: Airline Strategy Influences - Liasidou, Sotiroula (My University, 2013)
Recent developments in the airline industry have given rise to new types of tourists who differ in terms of the ways they devise their own travel itineraries. In particular, airline liberalisation has impacted the tourism industry with an array of strategic actions that involve pricing, service and operations. Admittedly, the main parameter of alteration relates to the consumption patterns whereby the consumer has become more knowledgeable and able to compose travel itineraries. This paper aims to identify and segment British tourists, who visit the Republic of Cyprus, in terms of their current consumption patterns according to recent airline and tourism developments, with a view to providing insights into the varied profiles of the tourists. Two-step cluster analysis is employed as the most appropriate method to identify and explain the market segmentation. The results of the cluster analysis reveal three main categories of tourists: 'traditional', 'demanding/opportunist' and 'ambivalent'. Each of the segments has several characteristics and the outcome of the study suggests that tourists as consumers are familiar with current advancements in both industries and indeed have the power to determine their holiday itineraries. The study is significant because it highlights the dynamic relationship between the two industries by means of exploring the ways in which the alteration of airline industry strategies has impacted tourism industry along with the consumption patterns and decision-making processes associated with it
Keywords: Airline strategies; Cluster analysis; Consumption patterns; Cyprus; Decision-making; LCCs; Neo-Fordism